Real options analysis course : business cases and software applications - Mun, Johnathan (Hoboken, N.J. : John Wiley, 2003)
A logical extension of the theory and application presented in Real Options Analysis. More specifically, the book presents numerous real options examples and provides the reader with step-by-step problem-solving techniques.
Installing the software -- Getting started with the software -- Framing real options -- The basics of financial modeling -- The basics of real options -- Real options business cases -- Extended problems -- Exercise solutions -- Real options tables.
Published simultaneously in Canada.
Includes appendix and index.
oif 02/09/15
Loan
System requirements for accompanying computer disc: Pentium II or higher processor, 64 MB of RAM, 75 MB hard-disk space, CD-ROM drive, SVGA monitor with 256 Color, Excel 2000, XP, or later and Windows 2000, XP, or later.
Keywords: Real options (Finance)